'I did not walk here all the way from prose': Ben Lerner's virtual poetics. Issue 2 (23rd February 2017) - Katz, Daniel
ABSTRACT: This paper argues that Ben Lerner's discussions of poetry and poetics in his two acclaimed novels, Leaving the Atocha Station and 10.04, have not received the serious attention they deserve. Here, I examine the novels as clear extensions of Lerner's poetic project as seen in his three volumes of 'verse', and link them to the theoretical discussions of poetics one finds in the prose of poets like Baudelaire, Rimbaud, Dickinson, or Pound. This in turn opens the way to seeing Lerner as engaged in an ongoing project in which neither prose nor poetry is privileged, but each dialogues with the other in what must be considered a serial prosimetrum. Following from this, I examine how the prose writings illuminate and enact the poetics of virtuality which Lerner favours and explores in many ways, not least of which being the displacement of poetry and poetics into novels, and the disturbing of the claims generally made for each genre. Ultimately, Lerner's opposition to 'mere actuality' or 'mere positivity' can only be understood if his novels are allowed to be disturbed by the volumes of poetry that surround them, rather than being left to stand as copious containers that might bound the poetic impulse.